A STUDY ON WORKING ENVIRONMENT INFLUENCING EMPLOYEE RETENTION OF INDIAN IT PROFESSIONALS - Gangwani, Dr. Sanjeevni; Dubey, Ms. Khushbu (IJRDO - Journal of Applied Management Science, 2016)
In today’s competitive scenario, as the awareness and technology play a vital role in developing the competition more essential and intense. Retention becomes one of the biggest issues for the IT industry of India because people are the one who generates profits and considered as the capital or asset of the organization. Employee retention is most decisive concern facing business leaders as a result of the shortage of skilled labour, economic growth and employee turnover. Retention is defined as “the ability to hold onto those employees you want to keep, for longer than your competitors In modern times, employee’s retention has become one of the leading challenges for organization. Given today’s weak company loyalty, employees are increasingly "jumping ship" for better job opportunities elsewhere. The issue isn’t simply losing a key member of your team; there is also the hassle-and cost-of replacement. It is obvious that employee’s retention is one of the most pressing issues that Human Resource Professionals face today. This research paper aims to examine the impact of working environment on employee retention in IT sector